2001
DOI: 10.1152/jappl.2001.91.1.218
|View full text |Cite
|
Sign up to set email alerts
|

Validity of inspiratory and expiratory methods of measuring gas exchange with a computerized system

Abstract: The accuracy of a computerized metabolic system, using inspiratory and expiratory methods of measuring ventilation, was assessed in eight male subjects. Gas exchange was measured at rest and during five stages on a cycle ergometer. Pneumotachometers were placed on the inspired and expired side to measure inspired (VI) and expired ventilation (VE). The devices were connected to two systems sampling expired O(2) and CO(2) from a single mixing chamber. Simultaneously, the criterion (Douglas bag, or DB) method ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
88
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(93 citation statements)
references
References 19 publications
3
88
0
2
Order By: Relevance
“…A validation study of this system found that the differences compared to the gold-standard Douglas bag method were 'so small as to be not physiologically significant'. 43 The affective dimension of pleasure-displeasure during exercise was assessed with the Feeling Scale (FS). 44 The FS is an 11-point, single-item, bipolar rating scale commonly used for the assessment of affective responses during exercise.…”
Section: Subjectsmentioning
confidence: 99%
“…A validation study of this system found that the differences compared to the gold-standard Douglas bag method were 'so small as to be not physiologically significant'. 43 The affective dimension of pleasure-displeasure during exercise was assessed with the Feeling Scale (FS). 44 The FS is an 11-point, single-item, bipolar rating scale commonly used for the assessment of affective responses during exercise.…”
Section: Subjectsmentioning
confidence: 99%
“…At this time, mixing chamber systems are intended for single-subject use only. The conventional system using the mixing chamber method has been developed to provide accurate measurements and the convenience of automated analysis 20,21) . Our new system shows time-series plots for all channels during collection on a single display.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there are considerable inconsistencies in using the Douglas bag assumptions that violate actual physiological function of the respiratory and collecting zones of the lung. Furthermore, the bags are made of PVC material, which is slightly permeable to the external air [3,7,8,12]. This mixing continues to the next expiration, as the first volume of air from the body is actually room air not alveolar air.…”
Section: Methods and Equipments For Indirect Calorimetrymentioning
confidence: 99%
“…Some researchers have noted that it is very difficult to remove all the air from the Douglas Bag and air leaking out during the removal process [8]. According to some recent work of Bassett et al [3], the time need to be flushed out the Douglas bag valve and tubing inflated oxygen and decreased carbon dioxide gas content of room air. This dead air space acts to decrease the overall sensitivity and accuracy of the system.…”
Section: Methods and Equipments For Indirect Calorimetrymentioning
confidence: 99%
See 1 more Smart Citation